ANALYSIS OF NARRATIVE ELEMENTS A CASE STUDY OF THE BIBLICAL STORY OF THE CRUCIFIXION OF JESUS AND THE DEATH OF JESUS - Sanggam Siahaan; Sara Stefani Malau; Deswita Fitriani Samosir; Kesmi Veronika Simanjuntak (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study delves into the narrative surrounding the crucifixion and death of Jesus Christ, examining it through historical, theological, and narrative perspectives. The aim is to comprehend its significance and the impact it has on the lives of Christians. The crucifixion of Jesus, a pivotal event in Christian belief, occurred under Roman authority in the first century, symbolizing not only physical suffering but also deep spiritual implications. The research scrutinizes a variety of biblical and extra-biblical sources related to the crucifixion, including the events leading up to Jesus' arrest, the legal trials he underwent, and his death on the cross. The study found that the narrative conflicts involve multiple parties and layers of complexity, with internal conflicts accounting for 9% and external conflicts constituting 45%. The theological exploration focuses on the role of the crucifixion in the atonement of humanity’s sins. The narrative analysis, on the other hand, concentrates on how the Gospels narrate this story, its influence on Jesus' early followers, and its ongoing relevance to contemporary Christian faith. The external conflicts are further categorized into conflicts between characters (18%), society (14%), nature (9%), and the supernatural (5%). The findings suggest that Jesus’ crucifixion and death have transformative significance, influencing both historical developments and the spiritual lives of his followers. These percentages not only quantify the conflicts but also underscore their importance in the narrative, offering a deeper understanding of these events from social, political, and theological perspectives.